Essential values in human greatness - Llanos Zuloaga, Martha (2024)
This essay continues the one published last year (Llanos, 2023) and deepens the understanding of the theme of Human Greatness linked to the field of Education and Human Development. Initially we proposed the importance of future Education population for the promotion of Values that have Human Greatness as their vision and we established the Family, School andCommunity trilogy. Thus, the groups studied and the identification of multiple values provide us with very valuable inputs in this field. Based on the proposals of Shalom Schwartz (1992), a social psychologist whose work in the area of values is highly recognized for his research worldwide and his identification of 10 fundamental values and the contributions of Viktor Frankl (1950), medical doctor and philosopher, creator of the Logotherapy, we wanted to make a significant contribution to a field that currently requires research and innovative alternatives in the face of the crisis of values that societies face worldwide.